2010
DOI: 10.1186/1757-2215-3-21
|View full text |Cite
|
Sign up to set email alerts
|

Leucine-rich alpha-2-glycoprotein-1 is upregulated in sera and tumors of ovarian cancer patients

Abstract: BackgroundNew biomarkers that replace or are used in conjunction with the current ovarian cancer diagnostic antigen, CA125, are needed for detection of ovarian cancer in the presurgical setting, as well as for detection of disease recurrence. We previously demonstrated the upregulation of leucine-rich alpha-2-glycoprotein-1 (LRG1) in the sera of ovarian cancer patients compared to healthy women using quantitative mass spectrometry.MethodsLRG1 was quantified by ELISA in serum from two relatively large cohorts o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
92
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(99 citation statements)
references
References 50 publications
5
92
0
Order By: Relevance
“…Although potential clinicopathologic associations have been demonstrated with LRG1 in multiple tumors, including ovarian (Andersen et al, 2010), lung (Li et al, 2011) and colon cancer (Ladd et al, 2012), little is known about the role of LRG1 in tumor cells and tumor development. In this study, we observed that LRG1 was highly expressed in Grade IV glioma cell lines, but was expressed at a relatively lower level in SHG-44 cells (F) Immunofluorescence staining was performed to observe the distribution of E-cadherin protein in glioma cells.…”
Section: Discussionmentioning
confidence: 98%
“…Although potential clinicopathologic associations have been demonstrated with LRG1 in multiple tumors, including ovarian (Andersen et al, 2010), lung (Li et al, 2011) and colon cancer (Ladd et al, 2012), little is known about the role of LRG1 in tumor cells and tumor development. In this study, we observed that LRG1 was highly expressed in Grade IV glioma cell lines, but was expressed at a relatively lower level in SHG-44 cells (F) Immunofluorescence staining was performed to observe the distribution of E-cadherin protein in glioma cells.…”
Section: Discussionmentioning
confidence: 98%
“…It is mainly produced by the liver cells in response to cancer, but its synthesis by OCa cells has also been documented [11]. The actual functions of LRG are still unknown, although the glycoprotein has been associated with cell adhesion, granulocytic differentiation, cell migration, cell survival, protein interaction and signal transduction [12]. The O -glycosylated protein was also proposed to be involved in the acute-phase response, since its level was reported to be elevated in patients with microbial infection, as well as those afflicted with several different cancers, including OCa [11].…”
Section: Discussionmentioning
confidence: 99%
“…The expression of LRG1 is elevated in the sera of patients with autoimmune diseases such as Crohn's disease, ulcerative colitis, and rheumatoid arthritis, and it is correlated with the disease status . Furthermore, recent studies have reported that LRG1 can be used as a biomarker in several types of cancer such as ovarian, lung, biliary tract, and hepatocellular carcinoma . Serum LRG1 is also detected in patients with malignancies and associated with progression of malignancies .…”
mentioning
confidence: 99%